Visiting Jackie And Marty Hijmans, Edwards, Colorado - Watkins, Howard::::::::: (1982)
On deck of Hijmans' home: Marty Hijman using circular saw to cut beam; Adam Watkins, Carey Hijman on tricycle, Christine Watkins and Jackie Hijmans visiting